IMPLEMENTASI PEMBELAJARAN AL-QUR’AN DALAM MEMBENTUK KARAKTER RELIGIUS ANAK DI TK THUMB KIDS, BANDAR LAMPUNG - Dwi Puji Lestari; Nopiana; Hanifah Indrayanah (Universitas Darunnajah, 2024)
As technology grows more sophisticated, the drier the religius character of children among teenagers around us. Education as a place to sow character needs to take preventive measures, ECCE as a basic level in education has a role to shape religius character as the foundation of early childhood. The purpose of this study is to describe the implementation of Qur'an teaching in shaping the religius character of children in TK Thumb Kids, Bandar Lampung. This research method uses descriptive qualitative research. Data collection techniques use observation, documentation, and interviews. Data analysis using reduction, data display, and conclusion drawing/verification. The results showed first, religius stimulation in children starting from planning including curriculum, lesson implementation plans, structuring the learning atmosphere, learning materials and media, learning methods and strategies to be used. Second, the implementation of Qur'an learning. Third, form a religius character. There are two inhibiting factors in the implementation of religius character, internal factors include children's laziness and lack of confidence. While external factors, the surrounding environment and peers. Keywords : Qur'an Learning, Religius Character, Early Childhood